On the correlation between micropore distribution obtained from molecular probes and from high resolution electron microscopy - Stoeckli, Fritz; Innes, R. W.; Fryer, J. R. (My University, 1989)
By using immersion calorimetry with liquids of various molecular dimensions, the distributions of the micropore sizes have been obtained for a number of active carbons, for the range 0.3 to 0.75 nm. These carbons have also been examined by high-resolution electron microscopy, the results from both techniques being displayed in the form of histograms. The agreement between the two methods appears to be good and provides possible evidence of the reduced interaction radius of adsorbed molecules and of exfoliation.
Keywords: Active carbon; micropore size distribution; immersion calorimetry; high-resolution electron microscopy